2012
DOI: 10.1159/000337870
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Management of a Primary Duodenal Carcinoid Tumor

Abstract: Carcinoids are rare, slow-growing tumors originating from a variety of different neuroendocrine cell types. They are identified histologically by their affinity for silver salts and by positive reactions to neuroendocrine markers such as neuron-specific enolase, synaptophysin and chromogranin. They can present with various clinical symptoms and are difficult to diagnose. We present the case of a 43-year-old woman who was referred for evaluation of anemia. Upper endoscopy showed a duodenal bulb mass around 1 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
3
3
0
Order By: Relevance
“…Most duodenal carcinoid tumors are nonfunctioning and therefore present as bowel obstruction, jaundice if peri-ampullary, mass effect or with metastatic disease [4, 5, 11, 12]. The results of our study also demonstrated similar to published reports that duodenal carcinoid tumors were more common in the proximal duodenum seen on CT in the first and second portions in 78.3% in our study [4].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Most duodenal carcinoid tumors are nonfunctioning and therefore present as bowel obstruction, jaundice if peri-ampullary, mass effect or with metastatic disease [4, 5, 11, 12]. The results of our study also demonstrated similar to published reports that duodenal carcinoid tumors were more common in the proximal duodenum seen on CT in the first and second portions in 78.3% in our study [4].…”
Section: Discussionsupporting
confidence: 90%
“…Ampullary masses frequently cause biliary obstruction, jaundice, and biliary dilation [8, 11]. This was also seen in our study as of the ten patients with ampullary carcinoid tumors in our study, six resulting in biliary obstruction and three also with mild pancreatic duct obstruction.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Once the tumour invades the serosa and involves the retroperitoneum it causes severe desmoplastic reaction leading to retroperitoneal fibrosis and subsequent urethral obstruction, peyronie’s disease of the penis, intra-abdominal fibrosis and occlusion of the mesenteric arteries or veins. In patients with duodenal carcinoid, carcinoid syndrome may occur in 4% 4. Our patient had typical features of carcinoid syndrome which is rare.…”
Section: Discussionmentioning
confidence: 53%
“…The majority of patients with small-bowel carcinoid tumors present with metastases to lymph nodes or the liver, and 5 % -7 % present with carcinoid syndrome [3]. As a result, the most important consideration in determining whether patients are candidates for endoscopic treatment is evaluation for metastatic disease [4]. Carcinoid tumors with evidence of lymphatic or distant metastases should not be treated by endoscopic resection [5].…”
Section: Endoscopic Mucosal Resection Of Duodenal Carcinoidmentioning
confidence: 99%